EFEK MODERASI DISIPLIN KERJA PADA PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DI KANTOR LEMBAGA LAYANAN PENDIDIKAN TINGGI (LLDIKTI) WILAYAH VIII - Made Yully Martiana Dewi (Journal of Applied Management Studies, 2021)
This study aims to determine the effect of the moderating effect of work discipline on the influence of motivation on employee performance in the Office of the Higher Education Institution (LLDIKTI) Region VIII. This research was conducted at the Office of the Higher Education Service Institution VIII Denpasar with a total sample of 59 people. The data obtained from the survey results were then analyzed using a variance based or component based approach with Warp Partial Least Square (PLS). The results showed that 1) motivation has a positive and significant effect on the performance of LLDikti Region VIII employees. This result means that an increase in providing motivation will be able to improve the performance of LLDikti Region VIII employees; 2) Work Discipline has a positive and significant effect on the performance of LLDikti Region VIII employees. This result means that an increase in work discipline will be able to improve the performance of LLDikti Region VIII employees; and 3) work discipline is not capable as a mediator variable in the relationship between motivation and performance of LLDikti Region VIII employees. This is because work discipline is a moderator predictor. Where work discipline is only as an independent variable, it cannot be a moderating variable. Overall research findings indicate that motivation and work discipline have an effect on employee performance. on the other hand, work discipline is not able to be a moderating variable in the relationship between motivation and employee performance.